2000
DOI: 10.1016/s0167-7322(99)00169-5
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of the hydrogen bond network of liquid water in a cylindrical SiO2 pore

Abstract: We present results of molecular dynamics simulations of water confined in a silica pore. A cylindrical cavity is created inside a vitreous silica cell with geometry and size similar to the pores of real Vycor glass. The simulations are performed at different hydration levels. At all hydration levels water adsorbs strongly on the Vycor surface; a double layer structure is evident at higher hydrations. At almost full hydration the modifications of the confinement-induced site-site pair distribution functions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
109
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 24 publications
(33 reference statements)
12
109
0
1
Order By: Relevance
“…It is generally believed that near the hydrophilic surface such as silica there is a 2-to 3-Å layer of water with about 10% higher density, whereas in the center of the pores water distributes uniformly (32,(55)(56)(57)(58)(59)(60)(61). When we compare the normalized particle structure factors of this core-shell cylinder and its average, we find that at around the Bragg peak position (Q ¼ 0.2 Å −1 ), the difference of thePðQÞ is about 5%.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…It is generally believed that near the hydrophilic surface such as silica there is a 2-to 3-Å layer of water with about 10% higher density, whereas in the center of the pores water distributes uniformly (32,(55)(56)(57)(58)(59)(60)(61). When we compare the normalized particle structure factors of this core-shell cylinder and its average, we find that at around the Bragg peak position (Q ¼ 0.2 Å −1 ), the difference of thePðQÞ is about 5%.…”
Section: Methodsmentioning
confidence: 86%
“…That is, the hydrophilic silanol surface provides a small and constant perturbation to the confined water. It is known that near the hydrophilic surface such as silica, there is a layer of denser water, whereas in the center of the pores water distributes uniformly (32,(55)(56)(57)(58)(59)(60)(61). The behavior of water near a hydrophobic surface may be different because of the lack of compensating hydrogen bonds from the surface and therefore requires more careful investigations (10,(58)(59)(60)62).…”
Section: Methodsmentioning
confidence: 99%
“…17,21,30 Several computer simulations have been also performed on water confined in different nanoporous materials. [31][32][33][34][35][36][37][38] These indicate that the diffusion dynamics of water, in the picosecond time scale, typically slows down near a nonattractive rough surface and speeds up near a nonattractive smooth surface. 39 Once confined in Vycor nanopores, 40 for example, water molecules exhibit at least two distinct regimes: a slow diffusion near the surface and a fast dynamics far away from the surface.…”
Section: Introductionmentioning
confidence: 98%
“…3 Moreover, the intermolecular correlations related to a preferential local structure within the fluid are probably affected by confinement 4 and peculiar features such as contact layers or orientation ordering have been invoked for some confinement conditions. 5,6,7 Confinement could eventually lead to new phases, the formation of which is driven by the balance between fluid-fluid and fluid-substrate interaction. 8 In the case of poor fluid-wall interaction, we have demonstrated that the change with pore size of the experimental structure factor of a confined fluid is dominated by topological constraints in terms of excluded volume effects.…”
Section: Introductionmentioning
confidence: 99%